PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI KANTOR CAMAT PASIR PENYU DI KABUPATEN INDRAGIRI HULU - Febrina, Dian (Eko dan Bisnis: Riau Economic and Business Review, 2022)
This research was conducted at the Pasir Penyu Camat Office in Indragiri Hulu Regency. The purpose of this study is to find out the Effect of the Work Environment on the Performance of Employees of the Camat Office Pasir Penyu in Indragiri Hulu Regency. This research place was conducted at the â€œPasir Penyuâ€ Camat Office in Indragiri Hulu Regency. The sample in the study was 32. Data analysis is done using validity tests, reliability, normality test, simple linear regression, R2 test and t test. The test is done to determine the relationship between free variables and bound variables. Based on the results of the study obtained a value of R square of 51.5% which shows that the work environment affects employee performance, while 48.5% is influenced by other variables that are not examined and the results of the t test conducted by the researchers obtained the value of t count (5.645 ) > t table (2,042). Thus it can be concluded that the work environment has a significant effect on the performance of employees of the Pasir Penyu Camat Office in Indragiri Hulu Regency